Congenital internal hernia in the neonate: Case series with review of potential comorbidities and imaging findings - Zachary Swenson; Dhara Kinariwala; Chioma Moneme; Eugene McGahren; Reza Daugherty (Elsevier, 2023)
Internal hernias are a rare but serious complication that typically present in older children and adults and can be congenital or iatrogenic in origin. They are often difficult to diagnose due to their similar radiological and clinical presentation to more common abdominal pathologies. We describe three cases of congenital internal hernias presenting in preterm infants followed by a literature review of congenital internal hernias presenting shortly after birth. When presenting in the neonatal period, congenital internal hernias have been exclusively reported as transmesenteric type. The exact etiology of transmesenteric congenital internal hernias is unclear, but may be a result of vascular compromise to the mesentery creating a small defect in which bowel may become entrapped. Certain genetic factors may also play a role in increasing risk for congenital internal hernias as they can be comorbid with other pathologies. Delayed diagnosis postpones surgical treatment, increasing risk of hernia incarceration, strangulation, irreversible bowel ischemia, and long-term risks inherent to bowel resection. Multimodal imaging plays a key role in the evaluation of these infants by excluding many causes of neonatal intestinal obstruction, however, a definitive prospective radiologic diagnosis has not been reported to date. Radiographic findings and comorbidities associated with these cases can be used along with future reported cases to potentially aid in timely diagnosis.